Chasing change : building organizational capacity in a turbulent environment - Thames, Robert C., 1946-; Webster, Douglas W., 1948- (Hoboken, N.J. : John Wiley & Sons, 2009)
"An essential resource for all agents of change, Chasing Change provides readers with the knowledge to understand the drivers of change as well as a practical toolset for meeting the change management needs tailored to each specific organization."--Jacket
Awareness. The Hurricane and the Earthquake -- Importance of Mindset -- Change Challenge Framework -- Crafting the Change Response -- Assessment. Assessing Capabilities for Change -- Leadership -- Commitment -- Accountability -- Forward Thinking -- Innovation -- Communication -- Risk Tolerance -- Organizational Learning -- Trust -- Diversity -- Empowerment -- Adaptation -- Dynamic Stability -- Change Journey and the Orchestration Process -- Assimilation. Executing the Change Plan -- Candor Bank -- 2005 Hurricane Katrina Catastrophe in New Orleans -- Conclusion -- About CAM-I.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Organizational change -- Management; Organizational change; Organizational Innovation; Changement organisationnel; BUSINESS & ECONOMICS -- Structural Adjustment; Organizational change; Organizational change -- Management; Organisationswandel; Organisatieverandering